Ahmadi Acute toxicity test using сyanide on Daphnia magna by flow-through system - Jaafarzadeh, N.; Hashempour, Y.; Angali, K. (Химия и технология воды, 2013)
This study describes the acute toxicity of sodium cyanide on the crustacean Daphnia magna (Cladocera). A new flow-through system was innovated in which the microorganism continuously exposure to the toxicity of sodium cyanide during the test. We used twelve different concentration of sodium cyanide from low values (0 mg CN/L) to high values (1 mg CN /L) on bioassay test. D. magna were exposed to the concentrations for 24, 48, 72 and 96 h at 20 – 25°C. We controlled the three important parameters such as temperature, pH and DO to meet the standard requirements. The LC₅₀ values for 24, 48, 72 and 96 h (95% confidence limits in parentheses) were estimated statistically by the probit methods and were 0.171 (0.163 – 0.179), 0.12 (0.112 – 0.128), 0.07 (0.062 – 0.078) and 0.019 (0.011 – 0.027) mg/L respectively. Finally, we proposed two new values for SAR (safe application rate) and SAFE Coefficients.